STEM-PjBL Worksheet : Ways to Improve Students' Collaboration, Creativity, and Computational Thinking - Shifa Alkautsar; Moh. Mirza Nuryady; Husamah Husamah; Poncojari Wahyono; Fuad Jaya Miharja (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to develop STEM-PjBL worksheets to improve students' collaboration, creativity, and computational thinking skills. This development research uses the ADDIE model by implementing all stages of development. The research instruments were student collaboration observation sheets, student creativity observation sheets, computational thinking assessment sheets, pretest and posttest questions, teacher interview sheets, and validation sheets. Data analysis techniques using qualitative and quantitative descriptive analysis. The product validation results show that the STEM-PjBL-based worksheet is categorized as very feasible based on the validation value obtained by the expert validator. Collaboration, creativity, and computational thinking skills scored respectively 83, 81, and 82 with very good level of achievement category. Non-parametric test results show a significance value (<0.05). These results indicate that the STEM-PjBL worksheet is very feasible and recommended for use in learning.